Pod igoto - Dakovski, Dako (Bulgaria : Studios for Feature Films, 1952)
Bulgaria is under the Ottoman yoke. Ivan Kralichat is going back from Diarbekir, where he has been imprisoned, to his home village of Byala Cherkva. In the village school an open class session is held. Rada Gospozhina's pupils feel uneasy with the questions that the Greek-minded Kiryak Stefchov puts to them. The new teacher Boycho Ognyanov interferes and helps the troubled girls. Doctor Sokolov and Ognyanov organise a secret uprising committee in the village. The representative from the town of Klisura meets with Ognyanov and promises support. The Turks learn from Kiryak Stefchov that Ognyanov is in fact the former prisoner Ivan Kralichat. They attempt to capture him in a church from where he manages to escape with the assistance of Kolcho the Blind. In Klisura, in the house of uncle Stoicho there is a gathering of young people who have fun. Meanwhile in the basement Ognyanov annonces the date of the uprising. The preparations gather full speed. Rada and Boycho Ognyanov pledge their love to each other. A treason has been committed and the uprising breaks earlier than planned. Klisura and Byala Cherkva are on fire. The uprising is mercilessly put down. Russia wages war on Turkey and Russian troops together with help from Bulgarian side liberate Bulgaria. People meet the victors with enthusiasm and celebrate the long-awated freedom.
Duration: 01:58:00
Keywords: Fiction films